PERMASALAHAN DALAM JUAL BELI ONLINE DI ERA DIGITAL - Goldwen, Filshella; Fernandha, Rizqy Dini; Kurnia, Ida (Universitas Kapuas, 2025)
The phenomenon of online buying and selling is growing rapidly along with advances in digital technology, providing various benefits such as efficiency, ease of access and market expansion. However, this development also brings a number of challenges, including digital fraud, delivery delays, and a lack of consumer protection. These problems not only harm consumers but also reduce trust in e-commerce as one of the pillars of the digital economy. This research uses a qualitative descriptive approach to identify the main factors that become problems in online buying and selling. In addition, this research explores solution steps that can be taken by governments, e-commerce platforms, and consumers to minimize existing risks. With legal foundations such as the Consumer Protection Law and Government Regulations on Trading Through Electronic Systems, this research aims to provide practical recommendations to create a safer, more transparent and fair e-commerce ecosystem for all parties.